KAJIAN PENAMBAHAN ASAM ASKORBAT PADA PENGKAYAAN Artemia sp. SEBAGAI PAKAN LARVA IKAN PATIN - Maria Gorety Eny Kristiany; Guntur Prabowo; Suharyadi Suharyadi (Universitas Mataram, 2021)
Based on the 2019 Cultivation Fisheries statistical data, the catfish commodity is one of the fishery commodities prioritized for development by the Ministry of Maritime Affairs and Fisheries. The pattern of rearing larvae to the production of catfish fry needs to be managed properly, especially in terms of feed. The natural food that is usually given as larvae feed is Artemia sp. Artemia enrichment with the addition of ascorbic acid is expected to increase the immunity of catfish larvae so that their survival increases as well. This study aims to examine the use of ascorbic acid as a nutrient enrichment material for artemia which is used as feed for catfish larvae. This study aims to examine the effect of ascorbic acid as an enrichment agent for Artemia sp. given as feed for catfish larvae. This research was conducted by comparing the survival and growth of catfish larvae fed with Artemia sp. which had been enriched by adding ascorbic acid and were fed artemia without ascorbic acid enrichment. Catfish larvae were reared in an aquarium container with a stocking density of 50 fish/L. The study was conducted on catfish larvae D2 to D15. Each treatment was repeated 5 times. Based on observations, it is known that catfish larvae fed Artemia feed enriched with ascorbic acid and without ascorbic acid produced growth that was not significantly different. However, catfish larvae fed Artemia feed enriched with ascorbic acid resulted in better survival and significantly different. ascorbic acid can be well absorbed by artemia sp. and is good given as an enrichment material for Artemia sp. which will be used as feed for catfish larvae.